1999
DOI: 10.1002/(sici)1097-4644(19991215)75:4<686::aid-jcb14>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the actin polymerization status as an apoptotic morphological effector in HL‐60 cells

Abstract: The alterations of the cytoskeletal actin network have been implicated as a morphological effector in apoptosis. However, studies directly linking actin change to the morphological events in apoptosis are lacking. This study quantitatively examined the effect of actin alteration on the camptothecin (CPT)-induced apoptotic process in HL-60 cells. Actin alteration was induced by two distinctive types of agent: the polymerization-stimulating agent, Jasplakinolide (Jas), and the polymerization-blocking agent, cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…21 In addition to the DNA fragmentation, changes to the actin cytoskeleton also implicate the possibility of PCD in the SI response, as the highly sustained actin depolymerization that accompanies SI 17 has been observed in several animal cells undergoing apoptosis. [18][19][20] Our electron microscopy data describing the morphological changes in pollen undergoing the SI response revealed none of the morphological hallmarks that typically characterize necrosis, such as loss of membrane integrity, cellular swelling or rupture. Even though we cannot rule out the possibility of secondary necrosis, our data are not inconsistent with the hypothesis that PCD may occur in SI challenged pollen tubes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In addition to the DNA fragmentation, changes to the actin cytoskeleton also implicate the possibility of PCD in the SI response, as the highly sustained actin depolymerization that accompanies SI 17 has been observed in several animal cells undergoing apoptosis. [18][19][20] Our electron microscopy data describing the morphological changes in pollen undergoing the SI response revealed none of the morphological hallmarks that typically characterize necrosis, such as loss of membrane integrity, cellular swelling or rupture. Even though we cannot rule out the possibility of secondary necrosis, our data are not inconsistent with the hypothesis that PCD may occur in SI challenged pollen tubes.…”
Section: Discussionmentioning
confidence: 99%
“…17 Intriguingly, long-term F-actin depolymerization has been identified as a feature of apoptosis. [18][19][20] Preliminary data suggesting that a programmed cell death (PCD) signalling cascade may be stimulated in the SI response was provided by evidence that DNA fragmentation, generally considered a hallmark in PCD, is stimulated in SI challenged pollen tubes. 21 This, together with similarities between the P. rhoeas SI system and the hypersensitive response (HR), which triggers a PCD cascade, has led to the idea that PCD may be triggered by the SI response.…”
Section: Introductionmentioning
confidence: 99%
“…18,20 Signalling downstream of Rho GTPases may contribute to both phases of actin reorganisation. During apoptosis, caspase-mediated cleavage of the Rho effector kinases PRK1 (also known as PKN) 54 and PRK2 55 as well as the Rac/Cdc42 effector kinase PAK2 (also known as g-PAK) 56,57 releases constitutively active kinase fragments.…”
Section: Second Phase: Breakdown Of Actin Structures and Apoptotic Bomentioning
confidence: 99%
“…However, numerous lines of evidence have demonstrated that the first phase of cell contraction and membrane blebbing (Figure 1) is a dynamic process associated with, and dependent upon, the presence of filamentous actin, 11 ± 23 increased myosin light chain (MLC) phosphorylation 15,16,19,22,24 and myosin ATPase activity. 15,16 After the initial phase of contraction and blebbing, a second phase of actin filament disassembly occurs via depolymerisation 18,20 and possibly through caspasemediated cleavage of actin monomers. 25 ± 27 First phase: contraction and blebbing active form of RhoA was shown to be sufficient for cell contraction and membrane blebbing.…”
Section: Introductionmentioning
confidence: 99%
“…Here, Ifound that CD82 can also inhibit migration through impairing actin cytoskeleton reorganization. Interestingly, disruption of cytoskeleton can trigger and accompany apoptosis (Rao et al, 1999). So far, whether CD82 inhibit cancer cell metastasis and trigger apoptosis through common pathway or different pathway remain unclear.…”
Section: Effect Of Kai1/cd82 Expression On Rac Effector Arp2/3mentioning
confidence: 76%